MANAGING INTERCULTURAL INTERACTION AND PREJUDICE OF THE INDONESIAN COMMUNITY: AS AN EFFORT TO PREVENT AND MANAGE SARA CONFLICT - Ferry Adhi Dharma (Informasi, 2018)
Interaction and conflict have a very close relationship. Besides, can cause conflicts, interactions can also be used to prevent and manage conflict. There are intrigue and prejudice in dynamic social interaction. Therefore, it takes control of that assessment to others, to be honest, and rational. Individually, prejudice can be controlled through one-way and two-way communication within the family. In groups, prejudice control can be done through the establishment of institutions to communicate more transactional. Social institutions can impose sanctions on anyone proven to produce and disseminate prejudices. Moreover, social institutions can also produce and deploy a symbol of harmony through myth or a true story. Interkasi dan konflik memiliki hubungan yang sangat erat. Disamping dapat menyebabkan konflik, interaksi juga dapat digunakan untuk mencegah dan menangani konflik. Ada intrik dan prasangka dalam interaksi sosial yang dinamis.  Oleh karena itu, dibutuhkan pengendalian agar penilaian terhadap orang lain menjadi jujur dan rasional. Secara individu, prasangka dapat dikendalikan melalui komunikasi satu dan dua arah dalam keluarga. Secara kelompok, pengendalian prasangka dapat dilakukan melalui pembentukan institusi yang dalam berkomunikasi lebih transaksional. Institusi sosial dapat memberi sanksi pada siapapun yang terbukti memproduksi dan menyebarkan prasangka. Selain itu, institusi sosial juga dapat memproduksi dan menyebarkan simbol kerukunan melalui mitos atau kisah nyata.